Gender Gaps in Achievement and Participation in Multiple Introductory Biology Classrooms - Eddy, Sarah L. (American Society for Cell Biology, 2014)
Although gender gaps have been a major concern in male-dominated science, technology, engineering, and mathematics disciplines such as physics and engineering, the numerical dominance of female students in biology has supported the assumption that gender disparities do not exist at the undergraduate level in life sciences. Using data from 23 large introductory biology classes for majors, we examine two measures of gender disparity in biology: academic achievement and participation in whole-class discussions. We found that females consistently underperform on exams compared with males with similar overall college grade point averages. In addition, although females on average represent 60% of the students in these courses, their voices make up less than 40% of those heard responding to instructor-posed questions to the class, one of the most common ways of engaging students in large lectures. Based on these data, we propose that, despite numerical dominance of females, gender disparities remain an issue in introductory biology classrooms. For student retention and achievement in biology to be truly merit based, we need to develop strategies to equalize the opportunities for students of different genders to practice the skills they need to excel.